Front-end design of low power radio access point for radio over fiber technology - Mohammed Al-Ahmadi, Abdullah Saad (2007)
Low-cost and easily-installed RAPs grew rapidly in popularity in the early 2000s. These devices offered a way to avoid the tangled messes of category 5 cable associated with typical Ethernet networks of the day. Whereas wiring a business, home, or school often requires stringing many cables through walls and ceilings, wireless networking offers the ability to reduce - or eliminate entirely - the stringing of cables. One IEEE 802.11 RAP can typically communicate with 30 client systems located within a radius of 100 m. However, the actual range of communication can vary significantly, depending on such variables as indoor or outdoor placement, height above ground, nearby obstructions, other electronic devices that might actively interfere with the signal by broadcasting on the same frequency, type of antenna, the current weather, operating radio frequency, and the power output of devices. Network designers can extend the range of RAPs through the use of repeaters and reflectors, which can bounce or amplify radio signals that ordinarily would go un-received. In experimental conditions, wireless networking has operated over distances of several kilometers. The purpose of this study is to design and simulate a Front-end design of low power radio access point for radio over fiber technology. Many simulations were performed using Microwave Office. The mean components were Power Amplifier PA and Band-pass Filter BPF. These two components were designed and simulated on frequency of 2.4 GHz.